Andinos y buenos cristianos. La inversión en lo sagrado en los trámites legales de dos caciques en el virreinato del Perú (siglo xvi) - Elfie Guyau (Journal de la Société des Américanistes)
From the second half of the 16th century onwards, the argument of exemplary Christian behaviour became a common rhetorical tool in the Andean caciques’ legal procedures. This article compares the legal procedures initiated by two Peruvian caciques between 1554 and 1575. We inquire why they did not represent their material investments in the sacred in their relaciones de méritos, to be identified as Christians. Contrasting the different procedures sheds light on the implicit norms used to represent the caciques’ Christian lives. It also illustrates what is at stake behind their identification as “exemplary Christians” by the colonial authorities. Moreover, the entanglement of elements taken from the Hispanic legal and political culture with more ancient forms and criteria of legitimacy enlightens how two indigenous lords balanced a new identity as Christian elites with their previous function in Andean communities by reformulating prehispanic practices and customs in the everyday life of their parishes.